Redesigning Job Descriptions and Job Specifications to Reduce Employee Turnover in Teman Lama Coffee Shop - Aprillia, Karina; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2020)
Abstract. Along with the changing trends that occur every year, this has an impact on people changing lifestyle. One form of this change is that coffee consumption has become a lifestyle of some communities which has led to the emergence of many coffee shops, one of which is Teman Lama. During their business development, Teman Lama experienced problems related to human resources. This indicated by the high employee turnover rate owned by the company. Based on preliminary study, it is known that the root of the problems experienced by Teman Lama lies in need to redesign the job analysis of each position consisting of job descriptions and job specifications. This is because employees often feel confused about doing their work and tend to do work outside their position which makes the burden they are carrying out exceeds what they are supposed to do. This happens because job analysis is not clear or even not owned by each position, thus triggering a constantly changing employee turnover rate. Therefore, this research helps Teman Lama to design job analysis that can solve their root problems. Teman Lama can also use job analysis into other human resource activities such as recruitment, performance appraisal, and compensation.Keywords: Job Analysis, Job Description, Job Specification, Employee turnover rate